Estetika Adegan Bondres Wayang Tantri oleh Dalang I Wayan Wija - I Dewa Ketut Wicaksandita; I Ketut Sariada; Hendra Santosa (PANGGUNG, 2020)
ABSTRACTBebondresan is a scene that is raised in order to entertain the audience. The scene of the bonding on theTantri puppet play Bhagawan Kundala Nangun Yadnya by Dalang Wija was brought up with a varietyof creativity that no other Dalang had ever done. This gave rise to appreciation in the form of applausefrom the audience who indicated the fulfillment of the wonderful taste of the aesthetic values that emerged.The main purpose of this research is to find out the aesthetics of the bebondresan scene. The researchmethod in the form of observation, interviews and documentation is the source of data acquisition by theauthor, which is then reduced and analyzed using instrumental aesthetic theory and aesthetic theoriesof aesthetics. The results of this study later found that the form of the bondres scene was formed visuallyin the form of three puppet Bondres namely, men holding drums, sexy women and agile old women,the structure consisted of three two-dimensional leather puppets, a drum and tambourine combinedthrough puppet play patterns, musical instruments and vocal wayang dialogues. The aesthetics of theBondres scene lies in, (1) ‘interrelations’, namely wholeness which is seen from the interrelationship,integration and harmony in the elements forming the scene; (2) ‘complexity’ that is interwoven betweenthe elements in the structure that are staged through complex playing patterns; (3) ‘prominence’ whichis the presentation of the results of the achievement of creativity by Dalang Wija which is seen from thecharacteristics of the artwork, the background of the mastermind’s abilities and his motivation.Keywords: Bondres Scene, Wayang Tantri, I Wayan WijaABSTRAKAdegan bondres merupakan sebuah adegan yang dimunculkan dengan tujuan untukmenghibur penonton. Adegan bondres pada wayang Tantri lakon Bhagawan Kundala NangunYadnya oleh Dalang Wija dimunculkan dengan beragam kreativitas yang tidak pernahdilakuakn Dalang lain. Hal ini memunculkan apresiasi berupa tepuk tangan dari penoton yangmengindikasikan terpenuhinya rasa nikmat indah atas nilai estetis yang muncul. Tujuan utamapenelitian ini ialah untuk mengetahui estetika dari adegan bebondresan. Metode penelitianberupa observasi, wawancara dan dokumentasi menjadi sumber perolehan data oleh penulisyang selanjunya direduksi dan dianlisis menggunakan teori estetika instrumental dan teoriestetika sifat estetis. Hasil penelitian ini selajutnya menemukan bahwa wujud adegan bondresini terbentuk secara visual berupa tiga wayang bondres yaitu, pria memegang kendang, wanitasexy dan wanita tua lincah, strukturnya terdiri atas tiga buah wayang kulit dua dimensi, sebuahkendang dan tamborin yang dikombinasi melalui pola bermain wayang, alat musik dan vokaldialog wayang. Estetika adegan bondres ini terletak pada, (1) ‘keterkaitan’ yaitu keutuhan yangdilihat dari keterkaitan, keterpaduan dan harmoni pada elemen-elemen pembentuk adegan;(2) ‘kerumitan’ yang terjalin di antara elemen-elemen pada struktur yang dipentaskan melaluipola bermain yang kompleks; (3) ‘penonjolan’ yaitu presentasi hasil pencapaian kreativitasoleh Dalang Wija yang dilihat dari ciri-ciri karya seni, latar belakang kemampuan dalang danmotivasinya.Kata Kunci: Adegan Bondres, Wayang Tantri, I Wayan Wija